Internalization of Anti-Corruption Values to Foster Integrity Among 6th Grade Elementary School Students - Siti Muniroh (ILAW, 2024)
The internalization of anti-corruption values in elementary education plays a crucial role in building a generation with strong integrity and moral character. This study aims to analyze how anti-corruption values are internalized among 6th grade elementary school students to foster honesty, responsibility, and discipline from an early age. The research employs a qualitative descriptive method with a case study approach, using data collection techniques such as observation, interviews, and documentation. The findings indicate that the internalization of anti-corruption values is most effective when integrated into daily learning activities and reinforced through teacher modeling, participatory learning methods, and consistent habituation practices. Students demonstrate better understanding and behavioral adaptation when values such as honesty and responsibility are contextualized in real-life classroom situations. The study also reveals that teachers play a central role as role models in shaping students’ moral behavior. However, challenges remain in ensuring consistency between school-based learning and the broader social environment. The study concludes that continuous, integrated, and collaborative efforts between schools, teachers, and parents are essential for the successful internalization of anti-corruption values in elementary education.